Complex analysis of GPR signalsfor the delineation of subsurface subtle features - Akinsunmade, Akinniyi; Tomecka-Suchoń, Sylwia; Pysz, Paweł (Geology, Geophysics and Environment, 2020)
In this paper, complex signal analyses of ground penetrating radar (GPR) field data over an area of farmland in Krakow were interpreted alongside the basic filtered field data. The farmland was simulated with var-ying degrees of soil compaction induced by tractor movement. The focus of the study was the delineation of in-herent characteristics of media through which the electromagnetic energy travelled. Fourteen GPR profiles were acquired from the area. The field data were subjected to pre- and post-processing prior to its the presentation and interpretation. Advance analysis operations on the field data which resorted in different attributes reveal more about the effects of the compaction on the soil than indicated by the basic filtered field data. Better resolution of subsurface layers boundary and lateral variation in the physical properties of the traversing media were well elu-cidated. The results have demonstrated that an advanced signal processing such as used in the study has ability to depict subtle characteristics of the propagating media.